Teaching mathematics at elementary and high school levels: Using games as teaching tools (Research, Society and Development, 2021)
The constant social and technological transformations of modern society demand that the Teaching of Mathematics be in continuous improvement, seeking pedagogical proposals that promote contextualized and critical learning. This work aims to reflect on the influence that methodological approaches in the Teaching of Mathematics have on the cognitive development of the student and how games can be presented as didactic resources in the teaching of mathematics. We used a qualitative methodology, of a descriptive, exploratory and analytical nature, through a bibliographic review, with data analysis based on qualitative arguments, using articles published on the Google Scholar platform between the years 2017 and 2021. The results demonstrate the pedagogical practices Mathematical Modeling, Problem-Based Learning and Remote Teaching, with prevalence of Traditional Pedagogical Practice in the teaching of mathematics. The use of playfulness with games in the teaching of mathematics was evidenced as an alternative pedagogical practice and reflections on rethinking the teaching infrastructure, subsidizing the teacher in possibilities and incentives in the application of new didactic methods such as the use of games. It is concluded that the teaching of mathematics prevails in traditional pedagogical practice and that changes in teaching methods are necessary, and cannot neglect the participation of the teacher as inseparable from the process. The use of games is presented as an alternative method and not a substitute for other teaching models.